1998
DOI: 10.1007/s002770050443
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and possible function of axl expression in immature human mast cells

Abstract: The receptor tyrosine kinase Axl which expresses extracellular domains reminiscent of cell adhesion molecules, is involved in homotypic binding as well as in intracellular signaling of myeloid progenitor cells. In order to investigate factors which might influence differentiation pathways through changes of the adhesive properties of cells, we analyzed the expression of axl in immature basophil and mast cell lines and in cultured basophil and mast cell precursors. Axl expression was induced by interferon-alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Alternatively, GAS6 may act as a chemoattractant (19). Hematopoietic cells of all lineages express Axl (29,30), and GAS6 produced by stromal cells could induce chemotaxis of Axl-expressing progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, GAS6 may act as a chemoattractant (19). Hematopoietic cells of all lineages express Axl (29,30), and GAS6 produced by stromal cells could induce chemotaxis of Axl-expressing progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…33 Several studies suggest that Axl plays a role in differentiation of early myeloid progenitors, 33 thymic stromal cells, 34 and mast cells. 35 In addition, a triple knockout of all Axl-family receptors exhibited lymphoproliferative abnormalities attributable to increased expression of proinflammatory cytokines by activated macrophages. 7 Similarly, our data showed that decreased survival and/or differentiation of intimal macrophages and neutrophils resulted in a greater neutrophil recruitment to the LCA adventitia of Axl Ϫ/Ϫ mice ( Figure 5F).…”
Section: Discussionmentioning
confidence: 99%
“…17 Autophosphorylation occurs through high-affinity interactions with Gas6, a secreted Gla-containing protein that shares significant amino acid homology with Protein S, a negative regulator of the coagulation cascade. 20,21 Axl has previously been detected in vitro in several cell types, including bone marrow stromal cells, 22 chondrocytes, 23 immature mast cells, 24 endothelial cells, 21,25,26 and vascular smooth muscle cells (VSMCs). 27 In vivo, Axl and Gas6 have been localized to articular cartilage, 23 rheumatoid arthritic synovium and synovial fluid, 28 and in the neointima of arteries after balloon injury.…”
Section: Discussionmentioning
confidence: 99%